Islamic Parenting as a Strategy for Shaping Children's Emotional Intelligence in a Review of Islamic Psychology - Sit, Masganti; Nur Rizkiya Makhfiro Nasution; Siti Aminah (The Future of Education Journal, 2025)
This study explores Islamic parenting patterns as a wise and purposeful approach to nurturing children’s emotional intelligence (EI), all under the gentle guidance of Islamic psychology. In today’s fast-paced modern life, children often struggle with feelings such as anxiety or difficulty in self-regulation, highlighting the growing importance of parenting methods that align with the core values and faith of Islam. The heart of this discussion is to explain how the timeless teachings of Islam rooted in the Qur’an, the Prophet’s sayings, and his lived example play a role in shaping emotional intelligence (EI), focusing on key aspects such as self-awareness, emotional regulation, intrinsic motivation, empathy, and social adaptability. Using a qualitative and in-depth approach, this work integrates insights from Islamic scriptures and psychological thought, along with open conversations with 25 devoted Muslim parents and child experts in Indonesia. The data were analyzed through careful thematic exploration to reveal everyday parenting practices that harmonize with the profound truths of Islam. The findings show that this parenting style characterized by rahmah (gentle compassion), tarbiyah (moral nurturing with tenderness), and tawazun (balance between firm guidance and warm affection) significantly enhances EI by fostering a spiritual pathway for managing difficult emotions. Children raised under these principles exhibit genuine resilience, deep empathy for others, and stronger social connections. These qualities were drawn directly from parents’ accounts of fewer emotional outbursts, smoother school days, and more harmonious relationships overall. Ultimately, this research illustrates how Islamic psychology meaningfully supports holistic child development both physically and spiritually and encourages the integration of these ideas into counseling frameworks for Muslim families.